Hypotheses for the Evolution of Reduced Reactive Aggression in the Context of Human Self-Domestication - Wrangham, Richard W. (Frontiers in Psychology, 2019)
Parallels in anatomy between humans and domesticated mammals suggest that for the last 300,000 years, Homo sapiens has experienced more intense selection against the propensity for reactive aggression than any other species of Homo. Selection against reactive aggression, a process that can also be called self-domestication, would help explain various physiological, behavioral and cognitive features of humans, including the unique system of egalitarian male hierarchy in mobile hunter-gatherers. Here I review nine leading proposals that could potentially explain why self-domestication occurred in H. sapiens, whether by selecting in favor of cooperation and tolerance or by selecting against aggressiveness. To account for the domestication syndrome, proposals must explain what led to a decline in fitness of highly aggressive males, and why the explanatory factor applies only to H. sapiens rather than to other species of Homo. The proposed explanations invoke genetic group selection; group-structured culture selection (also known as cultural group selection); social selection by female mate choice; social selection by male partner choice; increased self-control; cooperative breeding; high population density; use of lethal weapons; and language-based conspiracy. Most proposals face difficulties in accounting for the origins and/or maintenance of self-domestication. I conclude that the evolution of language-based conspiracy, which is a form of collective intentionality, was the key factor initiating and maintaining self-domestication in H. sapiens, because it is the most convincing mechanism for explaining the selective pressure against individually powerful fighters. Sophisticated language enabled males of low fighting prowess to coordinate in executing physically aggressive and domineering alpha males. This system is known today as a leveling mechanism in small-scale societies. Group-structured culture selection possibly accelerated the process.